Adsorption of the ionic liquid [BMP][TFSA] on Au(111) and Ag(111): substrate effects on the structure formation investigated by STM - Uhl, Benedikt; Buchner, Florian; Alwast, Dorothea; Wagner, Nadja; Behm, R. Jürgen (Beilstein Journal of Nanotechnology, 2013)
In order to resolve substrate effects on the adlayer structure and structure formation and on the substrate–adsorbate and adsorbate–adsorbate interactions, we investigated the adsorption of thin films of the ionic liquid (IL) 1-butyl-1-methylpyrrolidinium-bis(trifluoromethylsulfonyl)imide [BMP][TFSA] on the close-packed Ag(111) and Au(111) surfaces by scanning tunneling microscopy, under ultra high vacuum (UHV) conditions in the temperature range between about 100 K and 293 K. At room temperature, highly mobile 2D liquid adsorbate phases were observed on both surfaces. At low temperatures, around 100 K, different adsorbed IL phases were found to coexist on these surfaces, both on silver and gold: a long-range ordered (‘2D crystalline’) phase and a short-range ordered (‘2D glass’) phase. Both phases exhibit different characteristics on the two surfaces. On Au(111), the surface reconstruction plays a major role in the structure formation of the 2D crystalline phase. In combination with recent density functional theory calculations, the sub-molecularly resolved STM images allow to clearly discriminate between the [BMP]+ cation and [TFSA]− anion.
Keywords: adsorption; Ag; Au; [BMP][TFSA]; ionic liquids; scanning tunnelling microscopy; self-assembly